Experience of low dose magnesium Sulphate for the management of Eclampsia and its comparison with Pritchard regime - Supriya Suman; Prerna Jain; Manju Gita Mishra (International Journal of Medical Research and Review, 2016)
Objectives: To study the effectiveness, side effects, maternal and perinatal outcome, using low dose Magnesium sulphate and to compare the results with Pritchard regime.Methods: Thirty women with eclampsia aged between 25 to 35 years were prospectively studied over two years at M.G.M hospital & research center, Patna, Bihar. Study was designed into Group A who received low dose magnesium sulphate regime (n=15) and Group B who received standard Pritchard regime (n=15).Results: Groups were compared with respect to type of eclampsia, amount of dose of Magnesium sulphate and Signs of Toxicity of Magnesium sulphate. Magnesium sulphate received was 23gm in Group A and 44 gms in Group B and dose related toxicity was less in Group A. Perinatal morbidity and mortality was higher with Pritchard regime compared to low dose Magnesium sulphate regime.Conclusion: Low dose Magnesium sulphate is as effective as conventional full dose Pritchard regime with lesser side effects with equally good perinatal outcome.